Postpartum IUCD: its acceptance and complications - Garg, Nishi; Grover, Seema; Kaur, Bhupinder (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intra Uterine Contraceptive Device is the most commonly used reversible method of contraception worldwide. Immediate PPIUCD insertion is labelled when intra uterine device is inserted within 10 minutes to 48 hours of expulsion of placenta. The objective of the study was to determine the proportion of women accepting PPIUCD, factors influencing its acceptance, to look for side effects like bleeding disturbances, expulsion, lost strings, pain abdomen and pelvic infection etc. and the drop-out rates for follow up after PPIUCD. Methods: This was an open prospective, and longitudinal study to assess the safety and acceptance of the Multi-load when inserted within 10 minutes to 48 hours of placental expulsion. Results: During the period of January 2015 to November 2015 there were total 1624 deliveries in the said period in the department of Obstetrics and gynaecology of GGS Medical College and Hospital Faridkot. Out of these 714 delivered by LSCS and 910 delivered Vaginally. After excluding 470 patients were counselled, only 97 (20.64%) accepted PPIUCD. Out of these 67 (69%) patients had post placental insertion. 15.4% underwent immediate postpartum insertion. 15.4% got PPIUCD with cesarean section. (25.77%) patients had missing threads/strings, 12 (12.37%) patients had mild pain and 9 women (9.27%) had excessive discharge. Conclusions: PPIUCD is cost effective and a very safe means of contraception. Postpartum period is the period when patient is highly motivated for contraception and can be easily counselled. PPIUCD has a huge potentiality and abundant scope in India and if widely used it will have a strong impact on population control and will prevent unplanned pregnancy and its sequelae.